Komposisi Kertas Bekas dan Kulit Kacang Tanah dalam Pembuatan Kertas Daur Ulang - Retno Arif Utami; Haryono Haryono; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2015)
One of environmental issues that still a problem is waste. One of the waste sources is rempeyek industry in Pelem Madu, Imogiri, Bantul, Yogyakarta Province that produces solid waste in the form of peanut shells and has not yet been processed adequately. Peanut shells contain of 63,5 % cellulose which can be used as additional component in paper recycling process. The purpose of this research was to know the effect of five composition ratio of peanut shells towards the tensile strength and water absorption of the recycled papers, by conducting an experiment which followed post test only with control group design. From the measurement of paper tensile strength, the averages from five times replication for each composition ratio between used papers and peanut shells (i.e. ,1:0,5; 1:1,0; 1:1,5; 1:2,0; and 1:25) were: 0,519 N/mm; 0,751 N/mm; 0,777 N/mm; 0,905 N/mm and 1,118 N/mm, consecutively. Meanwhile, the obtained means from water absorption test for the same composition ratios, were: 71,4 mm; 72,2 mm; 72,8 mm; 65,2 mm and 57,2 mm, respectively. The One Way Anova test at 0,05 level of significance, yielded a p value < 0,001 which means that the composition ratio variation significantly influenced the tensile strength and the water absorption of the yielded papers. The best composition ratio for both parameters is 1:2,5 and it can be concluded that the more peanut shells were added to the process, the produced paper will gain the higher tensile strength and the more able to reduce water absorption.